Measuring Risk Aversion and the Wealth Effect - Frank Heinemann (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
Measuring risk aversion is sensitive to assumptions about the wealth in subjects' utility functions. Data from the same subjects in low- and high-stake lottery decisions allow estimating the wealth in a pre-specified one-parameter utility function simultaneously with risk aversion. This paper first shows how wealth estimates can be identified assuming constant relative risk aversion (CRRA). Using the data from a recent experiment by Holt and Laury (2002), it is shown that most subjects' behavior is consistent with CRRA at some wealth level. However, for realistic wealth levels most subjects' behavior implies a decreasing relative risk aversion. An alternative explanation is that subjects do not fully integrate their wealth with income from the experiment. Within-subject data do not allow discriminating between the two hypotheses. Using between-subject data, maximum-likelihood estimates of a hybrid utility function indicate that aggregate behavior can be described by expected utility from income rather than expected utility from final wealth and partial relative risk aversion is increasing in the scale of payoffs.
urn:nbn:de:bvb:19-epub-13395-7
Keywords: C81; C91; D81; 330; lottery choice; risk aversion; myopic risk aversion